Nano-fluid memristor based on AAO thin film and preparation method of nano-fluid memristor
By using AAO film and CuSO4 electrolyte in nanofluid memristors, the solid-liquid reaction of copper ions is used to achieve conductivity changes, which solves the problems of large working voltage, large energy consumption and complex preparation of existing nanofluid memristors, and achieves the goals of low power consumption and simple preparation.
Patent Information
- Application Number
- CN202411568385.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Existing nanofluid memristors face challenges such as large working voltage, large energy consumption, and complex preparation, and it is difficult to achieve the goals of low power consumption and simple preparation.
Using a nanofluid memristor based on AAO film, a PDMS liquid reservoir and CuSO4 electrolyte are provided on a glass substrate to achieve conductivity changes in the nanochannel array using solid-liquid reaction of copper ions, thereby generating a memristor effect.
It realizes a nanofluid memristor with small operating voltage, low power consumption and simple preparation, and its energy consumption is even lower than that of biological synapses. The high surface area and controllable pore size of the AAO film improve the stability of the device.
Smart Images

Figure CN119546175A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of micro-nano electronic devices, and in particular to a nanofluid memristor based on an AAO film and a preparation method thereof. Background Art
[0002] At this stage, digital computers are all based on the traditional von Neumann architecture, which is characterized by the separation of storage units and computing units. This separation hinders the rapid exchange and efficient processing of large amounts of data, thus forming a von Neumann bottleneck.
[0003] In biology, research has shown that the power consumption of the human brain is only about 20W, and it is compact and efficient in computing. In biological neural networks, neurons store information while also processing and transmitting it. Therefore, people hope to imitate the biological brain to develop a computing architecture that can integrate storage and computing, namely neuromorphic computing, to obtain a low-power computing method.
[0004] The emergence of memristor devices has accelerated the development of neuromorphic computing. Memristor is the fourth basic circuit element. Its concept was first proposed by Cai Shaotang in 1971 to represent the relationship between charge and magnetic flux. The resistance of a memristor changes with the change of the amount of charge that has passed through it in history, so it has memory, similar to the function of a biological synapse. In 2008, after HP Labs produced the first physical memristor, people tried to use memristors to simulate synaptic plasticity to realize the synaptic function in neural networks. The non-volatile nature of the device also determines that the weights of artificial neural networks based on memristors can still be maintained after power failure. Memristors have outstanding performance in high-density integration and fast response, providing key support for the performance improvement of neuromorphic computing.
[0005] At present, traditional solid-state memristors are often used as synapses in artificial neural networks, realizing a variety of neural network functions, but the power consumption of solid-state memristors is still difficult to reach the level of biological neurons. Most solid-state memristors rely on electron transmission in solid media, while in organisms, synapses use ions to transmit information in a liquid environment. Compared with electrons, ions are more diverse, have better biocompatibility and stronger anti-electromagnetic interference capabilities, so people began to try to simulate synapses and build memristors that use ion transmission at the nanoscale, namely nanofluid memristors. At present, nanofluid memristors based on different mechanisms such as ion adsorption, interface movement, and channel switching have been realized, but these nanofluid memristors still face challenges such as high operating voltage, high energy consumption, and complex preparation. Summary of the invention
[0006] The object of the present invention is to provide a nanofluid memristor based on an AAO film with low operating voltage, low power consumption, simple preparation and good stability, and a preparation method thereof.
[0007] The technical solution to achieve the purpose of the present invention is: a nanofluid memristor based on AAO film, comprising a glass substrate, a PDMS liquid reservoir, an AAO film, a CuSO 4 an electrolyte, a first copper electrode, and a second copper electrode;
[0008] The glass substrate is the bottom plate of the memristor, a first copper electrode is arranged on the glass substrate, a PDMS liquid reservoir is arranged on the first copper electrode, an AAO film is arranged in the PDMS liquid reservoir, and a CuSO 4 Electrolyte; a second copper electrode is arranged on the top of the PDMS reservoir; the first copper electrode, the AAO film, and the second copper electrode are connected in sequence;
[0009] The AAO film contains a plurality of nanochannels of set size, which are parallel but have different pore sizes at both ends, forming a nanochannel array, and the two ends of the nanochannel array are respectively connected to the first copper electrode and the second copper electrode;
[0010] The CuSO 4 The copper ions in the electrolyte can undergo a solid-liquid reaction with the inner wall of the nanochannel in the AAO film, causing the copper ions to be adsorbed onto the inner wall of the nanochannel;
[0011] The first copper electrode and the second copper electrode are used to apply voltage to both ends of the nanochannel array in the AAO film, so that the CuSO 4 The copper ions in the electrolyte enter or leave the nanochannel array, and the adsorption and desorption of the copper ions on the inner wall of the nanochannel causes the conductivity of the nanochannel array to change. This change has a lag compared to the voltage change applied by the electrode, thereby producing a memristor effect and realizing a nanofluid memristor based on AAO film.
[0012] Furthermore, the glass substrate has a thickness ranging from 1 to 2 mm, a length ranging from 7 to 8 cm, and a width ranging from 2 to 3 cm.
[0013] Furthermore, the PDMS liquid storage tank is made of polydimethylsiloxane, that is, PDMS material.
[0014] Furthermore, the AAO film is made of anodized aluminum, namely, AAO material.
[0015] Furthermore, in the AAO film, the density of the nanochannels is 280 pore·μm -2 , the average distance between the centers of two adjacent nanochannels is 60nm;
[0016] The geometry of a single nanochannel is asymmetric, with inconsistent pore sizes at both ends, average pore sizes ranging from 20 to 30 nm and 40 to 50 nm, respectively, a depth range of 50 to 60 μm, and a bullet-shaped cross section.
[0017] Furthermore, the number of the PDMS liquid reservoir is one, the shape is a cube, the length range is 5 to 20 mm, the width range is 5 to 15 mm, and the depth range is 1 to 3 mm.
[0018] Furthermore, the first copper electrode and the second copper electrode have a length range of 20 to 40 mm, a width range of 1 to 5 mm, and a thickness range of 0.1 to 0.2 mm, and are respectively placed on the lower end surface and the upper end surface of the PDMS liquid reservoir.
[0019] A method for preparing a nanofluid memristor based on an AAO film comprises the following steps:
[0020] Step 1, placing a first copper electrode at the center of a glass substrate, dropping colloidal PDMS onto the front end of the first copper electrode, and heating the glass substrate to accelerate the curing of PDMS;
[0021] Step 2: punching holes on the solidified PDMS layer using a puncher to obtain a PDMS liquid reservoir;
[0022] Step 3: Transfer the AAO film cut to a set size and containing the nanochannel array into the PDMS reservoir, so that the lower surface of the AAO film is attached to the front end of the first copper electrode on the glass substrate, and then fill the PDMS reservoir with CuSO 4 Electrolyte;
[0023] Step 4: Place a second copper electrode on the upper end of the PDMS reservoir, and then cover and seal the PDMS reservoir with PDMS.
[0024] Furthermore, the first copper electrode is placed at the center of the glass substrate as described in step 1, the colloidal PDMS is dripped onto the front end of the first copper electrode, and the glass substrate is heated to accelerate the curing of the PDMS, as follows:
[0025] Step 1.1, select the central position of the glass substrate, attach one end of the first copper electrode to the central position, and define this end as the front end, and the other end as the rear end, and the first copper electrode is horizontally attached to the glass substrate along the direction from the front end to the rear end;
[0026] Step 1.2, 0.5 mL of PDMS precursor and curing agent were fully mixed in a weight ratio of 10:1 to form a colloidal PDMS, the colloidal PDMS was allowed to stand to remove bubbles therein, and then the colloidal PDMS was drop-coated on the central part of the glass substrate, and the PDMS was naturally spread to cover the front end of the first copper electrode close to the center of the glass substrate;
[0027] Step 1.3: Place the glass substrate on a heating table and heat it. Set the heating temperature to 120° C. for 2 hours to accelerate the curing of the colloidal PDMS and finally form a cured PDMS layer.
[0028] Furthermore, in step 4, a second copper electrode is placed on the upper end of the PDMS reservoir, and then the PDMS reservoir is covered and sealed with PDMS, as follows:
[0029] Step 4.1, take another glass substrate, mix 0.5 mL of PDMS precursor and curing agent in a weight ratio of 10:1 to form a gel PDMS, let the gel PDMS stand to remove bubbles, then drop the gel PDMS on the central part of the glass substrate and wait for the PDMS to spread naturally;
[0030] Step 4.2, placing the glass substrate on a heating table to heat it, accelerating the curing of the gelatinous PDMS, and finally forming a cured PDMS layer;
[0031] Step 4.3: Peel off the cured PDMS layer from the glass substrate, align it with the top of the PDMS reservoir, and use PDMS to cover and seal the PDMS reservoir to prevent the CuSO in the PDMS reservoir from 4 The electrolyte evaporates.
[0032] Compared with the prior art, the present invention has the following significant advantages: (1) copper electrodes with relatively low standard electrode potential are used, so the operating voltage of the device is extremely small, about 20 mV. When working, the energy consumption of each nanochannel in the device is about 0.11 fJ / spike, while the average energy consumption of a single biological synapse is about 10 to 100 fJ / spike when working. The energy consumption of the device described in the present invention is even lower than that of the biological synapse; (2) AAO film has a high surface area, chemical inertness and controllable pore size. In the solution, abundant hydroxyl groups will be formed on the surface of the nanochannel, which has a good absorption effect on heavy metal ions; (3) The overall preparation process does not require complex equipment, and the preparation method is simple and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a structural schematic diagram of a nanofluid memristor based on AAO film of the present invention.
[0034] Figure 23 is a scanning electron microscope characterization image of the AAO nanochannel in an embodiment of the present invention.
[0035] Figure 3 4 is a current-voltage (IV) data curve of the nanofluid memristor in an embodiment of the present invention.
[0036] Figure 4 It is a graph of IV cycle data during the operation of the nanofluid memristor in an embodiment of the present invention.
[0037] Figure 5 Schematic diagram of the working principle of the nanofluid memristor in an embodiment of the present invention.
[0038] Figure 6 It is a data curve diagram of paired pulse enhancement PPF and paired pulse suppression PPD during the operation of the nanofluid memristor in the embodiment of the present invention.
[0039] Figure 7 It is a data curve diagram of short-term enhancement STF and short-term inhibition STD during the operation of the nanofluid memristor in the embodiment of the present invention. DETAILED DESCRIPTION
[0040] Combination Figure 1 The present invention discloses a nanofluid memristor based on an AAO film, comprising a glass substrate, a PDMS liquid reservoir, an AAO film, a CuSO 4 an electrolyte, a first copper electrode, and a second copper electrode;
[0041] The glass substrate is the bottom plate of the memristor, a first copper electrode is arranged on the glass substrate, a PDMS liquid reservoir is arranged on the first copper electrode, an AAO film is arranged in the PDMS liquid reservoir, and a CuSO 4 electrolyte; a second copper electrode is arranged on the top of the PDMS reservoir; the first copper electrode, the AAO film, and the second copper electrode are connected in sequence;
[0042] The AAO film contains a plurality of parallel nanochannels of a specific scale but with inconsistent pore sizes at both ends, forming a nanochannel array, and the two ends of the nanochannel array are respectively connected to the first copper electrode and the second copper electrode;
[0043] The CuSO 4 The copper ions in the electrolyte can undergo a solid-liquid reaction with the inner wall of the nanochannel in the AAO film, causing the copper ions to be adsorbed onto the inner wall of the nanochannel;
[0044] The first copper electrode and the second copper electrode are used to apply voltage to both ends of the nanochannel array in the AAO film, so that the CuSO 4The copper ions in the electrolyte enter or leave the nanochannel array, and the adsorption and desorption of the copper ions on the inner wall of the nanochannel causes the conductivity of the nanochannel array to change. This change has a lag compared to the voltage change applied by the electrode, thereby producing a memristor effect and realizing a nanofluid memristor based on AAO film.
[0045] As a specific example, the glass substrate has a thickness of millimeters, and a length and width of centimeters. Preferably, the glass substrate has a thickness of 1 to 2 mm, a length of 7 to 8 cm, and a width of 2 to 3 cm.
[0046] As a specific example, the PDMS liquid storage tank is made of polydimethylsiloxane, that is, PDMS material.
[0047] As a specific example, the AAO film is made of anodized aluminum, namely, AAO material.
[0048] As a specific example, in the AAO film, there are hundreds of nanochannels per square micron, and the average distance between the centers of two adjacent nanochannels is in the order of nanometers;
[0049] The geometry of a single nanochannel is asymmetric, the pore sizes at both ends are inconsistent, the average pore size at both ends is in the nanometer range, the depth is in the micrometer range, and the cross section is bullet-shaped. Preferably, the density of the nanochannels in the AAO film is 280 pore·μm -2 The average distance between the centers of two adjacent nanochannels is 60nm; the geometric shape of a single nanochannel is asymmetric, and the pore sizes at both ends are inconsistent. The average pore sizes at both ends range from 20 to 30nm and 40 to 50nm, respectively, the depth ranges from 50 to 60μm, and the cross section is bullet-shaped.
[0050] As a specific example, the number of the PDMS liquid reservoir is 1, the shape is a cube, and the length, width and depth are all in the order of millimeters. Preferably, the number of the PDMS liquid reservoir is 1, the shape is a cube, the length range is 5 to 20 mm, the width range is 5 to 15 mm, and the depth range is 1 to 3 mm.
[0051] As a specific example, the length, width and thickness of the first copper electrode and the second copper electrode are all in the order of millimeters, and are respectively placed on the lower end surface and the upper end surface of the PDMS liquid reservoir. Preferably, the length of the first copper electrode and the second copper electrode are both in the range of 20 to 40 mm, the width is in the range of 1 to 5 mm, and the thickness is in the range of 0.1 to 0.2 mm, and are respectively placed on the lower end surface and the upper end surface of the PDMS liquid reservoir.
[0052] The present invention also provides a method for preparing a nanofluid memristor based on an AAO film, comprising the following steps:
[0053] Step 1: Place the first copper electrode in the center of the glass substrate, drop the colloidal PDMS onto the front end of the first copper electrode, and heat the glass substrate to accelerate the curing of the PDMS, as follows:
[0054] Step 1.1, Step 1.1, select the central position of the glass substrate, attach one end of the first copper electrode to the central position, and define this end as the front end, and the other end as the rear end, and the first copper electrode is horizontally attached to the glass substrate along the direction from the front end to the rear end;
[0055] Step 1.2, 0.5 mL of PDMS precursor and curing agent were fully mixed in a weight ratio of 10:1 to form a colloidal PDMS, the colloidal PDMS was allowed to stand for a period of time to remove bubbles therein, and then the colloidal PDMS was drop-coated on the central part of the glass substrate, and the PDMS was naturally spread to cover the front end of the first copper electrode;
[0056] Step 1.3: Place the glass substrate on a heating table and heat it. Set the heating temperature to 120° C. for 2 hours to accelerate the curing of the colloidal PDMS and finally form a cured PDMS layer.
[0057] Step 2: punching holes on the solidified PDMS layer using a puncher to obtain a PDMS liquid reservoir;
[0058] Step 3: Transfer the AAO film cut into a specific size and containing the nanochannel array into the PDMS reservoir so that its lower surface fits the front end of the first copper electrode on the glass substrate, and then fill the PDMS reservoir with CuSO 4 Electrolyte;
[0059] Step 4: Place a second copper electrode on the upper end of the PDMS reservoir, and then cover and seal the PDMS reservoir with PDMS, as follows:
[0060] Step 4.1, take another glass substrate, mix 0.5 mL of PDMS precursor and curing agent in a weight ratio of 10:1 to form a gel PDMS, let the gel PDMS stand for a while to remove bubbles, then drop the gel PDMS on the central part of the glass substrate and wait for the PDMS to spread naturally;
[0061] Step 4.2, placing the glass substrate on a heating table to heat it, accelerating the curing of the gelatinous PDMS, and finally forming a cured PDMS layer;
[0062] Step 4.3: Peel off the cured PDMS layer from the glass substrate, align it with the top of the PDMS reservoir, and use PDMS to cover and seal the PDMS reservoir to prevent the CuSO in the PDMS reservoir from4 The electrolyte evaporates.
[0063] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0064] Example
[0065] Combination Figure 1 This embodiment provides a glass substrate, a PDMS liquid reservoir, an AAO film, a CuSO 4 an electrolyte, a first copper electrode, and a second copper electrode;
[0066] The glass substrate is the bottom plate of the memristor, a first copper electrode is arranged on the glass substrate, a PDMS liquid reservoir is arranged on the first copper electrode, an AAO film is arranged in the PDMS liquid reservoir, and a CuSO 4 Electrolyte; a second copper electrode is arranged on the top of the PDMS reservoir; the first copper electrode, the AAO film, and the second copper electrode are connected in sequence;
[0067] The AAO film contains a plurality of parallel nanochannels of a specific scale but with inconsistent pore sizes at both ends, forming a nanochannel array, and the two ends of the nanochannel array are respectively connected to the first copper electrode and the second copper electrode;
[0068] The CuSO 4 The copper ions in the electrolyte can undergo a solid-liquid reaction with the inner wall of the nanochannel in the AAO film, causing the copper ions to be adsorbed onto the inner wall of the nanochannel;
[0069] The first copper electrode and the second copper electrode are used to apply voltage to both ends of the nanochannel array in the AAO film, so that the CuSO 4 The copper ions in the electrolyte enter or leave the nanochannel array, and the adsorption and desorption of the copper ions on the inner wall of the nanochannel causes the conductivity of the nanochannel array to change. This change has a lag compared to the voltage change applied by the electrode, thereby producing a memristor effect and realizing a nanofluid memristor based on AAO film.
[0070] As a specific example, the glass substrate has a thickness of 1 mm, a length of 7.6 cm, and a width of 2.5 cm.
[0071] As a specific example, the PDMS liquid storage tank is made of polydimethylsiloxane, that is, PDMS material.
[0072] As a specific example, the AAO film is made of anodized aluminum, namely, AAO material.
[0073] As a specific example, the density of the nanochannels in the AAO film is 280 pore·μm -2, the average distance between the centers of two adjacent nanochannels is 60nm;
[0074] The geometry of a single nanochannel is asymmetric, with inconsistent pore sizes at both ends. The average pore sizes at the two ends are 24nm and 40nm, respectively, the depth is 56μm, and the cross-section is bullet-shaped.
[0075] As a specific example, there is one liquid reservoir in a cubic shape with an average length of 10 mm, an average width of 7 mm, and an average depth of 2 mm; the electrolyte injected into the liquid reservoir is CuSO 4 Solution, concentration is 1M.
[0076] As a specific example, the first copper electrode and the second copper electrode have a thickness of 0.1 mm, a length of 30 mm, and a width of 2 mm, and are placed on the lower end surface and the upper end surface of the PDMS liquid reservoir, respectively.
[0077] A method for preparing a nanofluid memristor based on an AAO film comprises the following steps:
[0078] Step 1: Place the first copper electrode at the center of the glass substrate, drop the colloidal PDMS onto the front end of the first copper electrode, and heat the glass substrate to accelerate the curing of the PDMS, as follows:
[0079] Step 1.1, placing a first copper electrode on a glass substrate, with its front end placed in the center of the glass substrate;
[0080] Step 1.2, 0.5 mL of PDMS precursor and curing agent were fully mixed in a weight ratio of 10:1 to form a colloidal PDMS, the colloidal PDMS was allowed to stand for a period of time to remove bubbles therein, and then the colloidal PDMS was drop-coated on the central part of the glass substrate, and the PDMS was naturally spread to cover the front end of the first copper electrode;
[0081] Step 1.3: Place the glass substrate on a heating table and heat it. Set the heating temperature to 120° C. for 2 hours to accelerate the curing of the colloidal PDMS and finally form a cured PDMS layer.
[0082] Step 2: punching holes on the solidified PDMS layer using a puncher to obtain a PDMS liquid reservoir;
[0083] Step 3: Transfer the AAO film cut into a specific size and containing the nanochannel array into the PDMS reservoir so that its lower surface fits the front end of the first copper electrode on the glass substrate, and then fill the PDMS reservoir with CuSO 4 Electrolyte;
[0084] Step 4: Place a second copper electrode at a position 1 mm horizontally away from the upper end surface of the PDMS reservoir and the first copper electrode, and then cover and seal the PDMS reservoir with PDMS, as follows:
[0085] Step 4.1, take another glass substrate, mix 0.5 mL of PDMS precursor and curing agent in a weight ratio of 10:1 to form a gel PDMS, let the gel PDMS stand for a while to remove bubbles, then drop the gel PDMS on the central part of the glass substrate and wait for the PDMS to spread naturally;
[0086] Step 4.2, placing the glass substrate on a heating table to heat it, accelerating the curing of the gelatinous PDMS, and finally forming a cured PDMS layer;
[0087] Step 4.3: Peel off the cured PDMS layer from the glass substrate, align it with the top of the PDMS reservoir, and use PDMS to cover and seal the PDMS reservoir to prevent the CuSO in the PDMS reservoir from 4 The electrolyte evaporates.
[0088] In this embodiment, there are multiple parallel nanochannels in the AAO film, as shown in the schematic diagram. Figure 1 , SEM characterization diagram reference Figure 2 The nanochannel has an asymmetric geometry, which is mainly manifested in the inconsistency of the pore diameters at the upper and lower ends. Figure 2 As shown in a and b, the average pore diameters of the upper and lower surfaces are 24 nm and 40 nm respectively, the channel depth is 56 μm, and the cross section is bullet-shaped. The cross-sectional SEM characterization of the AAO film is shown in Figure 2 As shown in c and d, the average spacing between two adjacent nanochannel holes is 60 nm.
[0089] In this embodiment, the current variation of the nanofluid memristor based on the AAO film in the DC scanning mode (0→20mV→0→-20mV→0) is as follows: Figure 3 As shown. From the corresponding IV curve, it can be seen that the change of current with voltage presents a self-crossing curve, which is a typical bipolar memristive behavior in memristive devices. During the scanning process from the crossover point to the 20mV voltage range, the device's conductance gradually increases from low to high, and during the scanning process from the crossover point to the -20mV voltage range, the device's conductance gradually decreases from high to low. This result proves that the device has a memristive effect.
[0090] Combination Figure 4 When the voltage scanning range of the AAO film-based nanofluid memristor is 0→20mV→0→-20mV→0, the device can still maintain a stable memristive effect in a 40-time cycle scanning test.
[0091] Combination Figure 5 The working principle of the nanofluid memristor is that the copper ions in the electrolyte will be adsorbed or desorbed by the inner wall of the nanochannel in the nanochannel array, resulting in the device producing two states of high conductance and low conductance, as follows: The inner wall of the nanochannel in the AAO film will adsorb CuSO 4 Copper ions in the electrolyte, such as Figure 5 As shown in ①. When a negative bias voltage is applied, under the action of the external electric field, CuSO 4 The copper ions in the electrolyte will migrate to the nanochannel array in the AAO film, and the inner wall of the nanochannel will continue to adsorb the copper ions in the electrolyte until it reaches saturation. Figure 5 As shown in ②, the copper ion flux in the nanochannel gradually increases, causing the device to become a high-conductance state. When a positive bias voltage is applied, the copper ions in the electrolyte will gradually leave the nanochannel array along the direction of the external electric field, as shown in Figure 5 As shown in ③, the copper ions adsorbed on the inner wall of the nanochannel are gradually desorbed. The copper ion flux in the nanochannel gradually decreases until there are almost no copper ions in the channel, as shown in Figure 5 As shown in ④, the device changes to a low conductance state.
[0092] The hysteresis effect of the IV curve is because when the applied voltage is changed in a specific step size, the rate at which the ions in the electrolyte are redistributed according to the direction of the external electric field is slow, resulting in hysteresis. When the scan rate, that is, the step size of the applied potential change is low, the hysteresis loop of the IV curve is normal. When the scan rate is fast, the ions in the nanochannel do not have enough time to migrate and redistribute, which makes it difficult for the device conductivity to change and the hysteresis loop area of the IV curve is reduced.
[0093] Combination Figure 6 and Figure 7 The nanofluid memristor provided in this embodiment can simulate the short-term plasticity of biological synapses. In the biological nervous system, synapses are responsible for connecting two neurons, and the short-term plasticity of synapses is the characteristic of synapses temporarily changing their own connection weights in order to transmit neuronal signals. This is the basic neural function of the brain for learning and memory.
[0094] Specifically, Figure 6 As shown in a, when two consecutive triangular wave voltage pulses are applied to the device, the pulse voltage U = 0.5V, and the pulse duration T = 0.2ms, the absolute value of the current induced by the second voltage pulse is lower than the absolute value of the current induced by the first voltage pulse; Figure 6As shown in Fig. 2a, when two consecutive triangular wave pulses, U = -0.5V, T = 0.2ms, are applied to the device, the absolute value of the current induced by the second voltage pulse is higher than that induced by the first voltage pulse; when the pulse interval ΔT of the two triangular wave voltage pulses gradually increases from 20μs to 40.96ms, as shown in Fig. Figure 6 As shown in Fig. c, when U = 0.5 V and T = 0.2 ms, the difference between the absolute values of the ion currents caused by the two pulses first decreases rapidly and then gradually decreases. This is the PPD phenomenon. On the other hand, Figure 6 As shown in Figure d, when U = -0.5V and T = 0.2ms, the difference between the absolute values of the ion currents caused by the two pulses increases rapidly at first, reaches a peak value at around 1.28ms, and then gradually decreases. This is a non-monotonic PPF phenomenon. The PPD phenomenon and the PPF phenomenon are the basic parts of the short-term plasticity of synapses. The retention time refers to the time required for the difference between the absolute values of the ion currents caused by the two pulses to decay to 5% of its maximum value. The retention time in biological synapses is generally between ten and hundreds of milliseconds. The retention time of the nanofluid memristor in the present invention is 55.6ms in the PPF process and 19.5ms in the PPD process.
[0095] like Figure 7 As shown in the figure, when multiple continuous triangular wave pulses are applied to the device, the number of pulses N = 50, U = ±0.5V, T = 0.2ms, ΔT = 50μs, the conductivity of the device will increase or decrease with the application of the pulse signal, proving that the nanofluid memristor based on AAO film has short-term conductivity adjustability, namely STF and STD. STF and STD are components of the short-term plasticity of biological synapses, so the nanofluid memristor based on AAO film has short-term plasticity and has broad prospects in neuromorphic computing applications.
[0096] The energy consumption of the nanofluid memristor based on AAO film provided in this embodiment can be estimated by the formula W=UIT / 2N′. When the pulse voltage U is 0.5V, the current I is 120μA, and the pulse duration T is 0.2ms, the number of parallel channels N′ is about 5.55×10 7 According to the formula, the energy consumption of a single nanochannel is about 0.11fJ / spike, which is the lowest energy consumption among all current nanofluidic memristors, and even better than the 10-100fJ energy consumption of biological synapses. These results prove that nanofluidic memristors based on AAO films have broad potential in neuromorphic computing applications.
[0097] The above are only preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A nanofluid memristor based on AAO film, characterized in that: It includes a glass substrate, a PDMS liquid reservoir, an AAO film, a CuSO4 electrolyte, a first copper electrode and a second copper electrode; The glass substrate is the bottom plate of the memristor, a first copper electrode is arranged on the glass substrate, a PDMS reservoir is arranged on the first copper electrode, an AAO film is arranged in the PDMS reservoir, and a CuSO4 electrolyte is filled; a second copper electrode is arranged on the top of the PDMS reservoir; the first copper electrode, the AAO film, and the second copper electrode are connected in sequence; The AAO film contains a plurality of nanochannels of set size, which are parallel but have different pore sizes at both ends, forming a nanochannel array, and the two ends of the nanochannel array are respectively connected to the first copper electrode and the second copper electrode; The copper ions in the CuSO4 electrolyte can undergo a solid-liquid reaction with the inner wall of the nanochannel in the AAO film, so that the copper ions are adsorbed onto the inner wall of the nanochannel; The first copper electrode and the second copper electrode are used to apply voltage to both ends of the nanochannel array in the AAO film, so that copper ions in the CuSO4 electrolyte enter or leave the nanochannel array under the drive of the electric field. The conductance of the nanochannel array changes through the adsorption and desorption of copper ions on the inner wall of the nanochannel. This change has a lag compared to the voltage change applied by the electrode, thereby generating a memristor effect and realizing a nanofluid memristor based on the AAO film.
2. The nanofluid memristor based on AAO film according to claim 1, characterized in that: The glass substrate has a thickness ranging from 1 to 2 mm, a length ranging from 7 to 8 cm, and a width ranging from 2 to 3 cm.
3. The nanofluid memristor based on AAO film according to claim 1, characterized in that: The PDMS liquid storage tank is made of polydimethylsiloxane, that is, PDMS material.
4. The nanofluid memristor based on AAO film according to claim 1, characterized in that: The AAO film is made of anodized aluminum, namely, AAO material.
5. The nanofluid memristor based on AAO film according to claim 1, characterized in that: In the AAO film, the density of nanochannels is 280 pore·μm -2 , the average distance between the centers of two adjacent nanochannels is 60nm; The geometry of a single nanochannel is asymmetric, with inconsistent pore sizes at both ends, average pore sizes ranging from 20 to 30 nm and 40 to 50 nm, respectively, a depth range of 50 to 60 μm, and a bullet-shaped cross section.
6. The nanofluid memristor based on AAO film according to claim 1, characterized in that: The number of the PDMS liquid storage pool is one, the shape is a cube, the length range is 5 to 20 mm, the width range is 5 to 15 mm, and the depth range is 1 to 3 mm.
7. The nanofluid memristor based on AAO film according to claim 1, characterized in that: The first copper electrode and the second copper electrode have a length range of 20 to 40 mm, a width range of 1 to 5 mm, and a thickness range of 0.1 to 0.2 mm, and are respectively placed on the lower end surface and the upper end surface of the PDMS liquid reservoir.
8. A method for preparing a nanofluid memristor based on an AAO film as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Step 1, placing a first copper electrode at the center of a glass substrate, dropping colloidal PDMS onto the front end of the first copper electrode, and heating the glass substrate to accelerate the curing of PDMS; Step 2: punching holes on the solidified PDMS layer using a puncher to obtain a PDMS liquid reservoir; Step 3, transferring the AAO film cut into a set size and containing the nanochannel array into the PDMS reservoir, so that the lower surface of the AAO film is in contact with the front end of the first copper electrode on the glass substrate, and then filling the PDMS reservoir with CuSO4 electrolyte; Step 4: Place a second copper electrode on the upper end of the PDMS reservoir, and then cover and seal the PDMS reservoir with PDMS.
9. The method for preparing a nanofluid memristor based on an AAO film according to claim 8, characterized in that: As described in step 1, a first copper electrode is placed at the center of the glass substrate, a gelatinous PDMS is dripped onto the front end of the first copper electrode, and the glass substrate is heated to accelerate the curing of the PDMS, as follows: Step 1.1, select the central position of the glass substrate, attach one end of the first copper electrode to the central position, and define this end as the front end, and the other end as the rear end, and the first copper electrode is horizontally attached to the glass substrate along the direction from the front end to the rear end; Step 1.2, 0.5 mL of PDMS precursor and curing agent were fully mixed in a weight ratio of 10:1 to form a colloidal PDMS, the colloidal PDMS was allowed to stand to remove bubbles therein, and then the colloidal PDMS was drop-coated on the central part of the glass substrate, and the PDMS was naturally spread to cover the front end of the first copper electrode close to the center of the glass substrate; Step 1.3: Place the glass substrate on a heating table and heat it. Set the heating temperature to 120° C. for 2 hours to accelerate the curing of the colloidal PDMS and finally form a cured PDMS layer.
10. The method for preparing a nanofluid memristor based on an AAO film according to claim 8, characterized in that: In step 4, a second copper electrode is placed on the upper end of the PDMS reservoir, and then the PDMS reservoir is covered and sealed with PDMS, as follows: Step 4.1, take another glass substrate, mix 0.5 mL of PDMS precursor and curing agent in a weight ratio of 10:1 to form a gel PDMS, let the gel PDMS stand to remove bubbles, then drop the gel PDMS on the central part of the glass substrate and wait for the PDMS to spread naturally; Step 4.2, placing the glass substrate on a heating table to heat it, accelerating the curing of the gelatinous PDMS, and finally forming a cured PDMS layer; Step 4.3, peel off the cured PDMS layer from the glass substrate, align it to cover the upper end of the PDMS reservoir, and use PDMS to cover and seal the PDMS reservoir to prevent the CuSO4 electrolyte in the PDMS reservoir from volatilizing.
Citation Information
Patent Citations
A liquid memristor and its preparation method and application
CN109146068A
Interface memristor based on nanofluid and preparation and application of interface memristor
CN110165049A
Preparation method of high-performance memristor with memristor coupling capacitance effect
CN113314668A
Grid-controlled interface type nanofluid memristor and preparation method thereof
CN113948636A
Liquid memristor and preparation method thereof
CN115915774A